Development of Scientific Based Interactive Learning Media With Lectora Inspire Substance Pressure Material - Saputri, Renny; Prasetyo, Wahyu Dwi (Program Magister Teknologi Pendidikan Universitas Jambi, 2015)
This research aims to develop scientific-based interactive science learning media with Lectora Inspire material on pressure of substances and its application and determine the perceptions of class VIII students at SMPN 11 Muaro Jambi towards the learning media developed. The test subjects in this research were class VIII students at SMPN 11 Muaro Jambi. The qualitative data analysis technique uses qualitative descriptive methods. The results of the research are in the form of scientific-based interactive science learning media with Lectora Inspire material on pressure of substances and its application for junior high school students. The final media product is in audio visual form in .exe format. This media contains material with text displays, images, animations, simulations and videos. This learning media is scientific-based so that every time the material is delivered it uses scientific learning steps. The advantage of this media is that how to operate this media is quite easy and simple. This media is classified as interactive because there is a reciprocal relationship between the user and the media and can be used offline. Obtaining expert assessments and student perceptions shows that this product is worthy of development.